Inside Front Cover: Plasma Process. Polym. 6/2021. Issue 6 (4th June 2021) - Wang, Cong; Fu, Qiang; Chang, Zhengshi; Zhang, Guanjun
Abstract : Inside Front Cover : CO2, which widely exists in Martian atmosphere, can be converted into O2 and fuel in‐situ. The in‐situ utilization of the abundant CO2 resources will support the construction of Mars energy base. The conversion method based on plasma technology is expected to activate and transform CO2 molecules under mild conditions. The oxygen can be used for astronauts to breathe and the fuel will be stored to power the launcher or lander as well as the many activities on Mars. Further details can be found in the article by Cong Wang, Qiang Fu, Zhengshi Chang, and Guanjun Zhang (e2000228 ).